2020
DOI: 10.30802/aalas-jaalas-18-000143
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic Modulation of Noxious Stimulus-evoked Brain Activation in Cynomolgus Macaques Observed with Functional Neuroimaging

Abstract: Maintaining effective analgesia during invasive procedures performed under general anesthesia is important for minimizing postoperative complications and ensuring satisfactory patient wellbeing and recovery. While patients under deep sedation may demonstrate an apparent lack of response to noxious stimulation, areas of the brain related to pain perception may still be activated. Thus, these patients may still experience pain during invasive procedures. The current study used anesthetized or sedated cynomolgus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 88 publications
0
9
1
Order By: Relevance
“… 53 In a previous study in naïve macaques, significant activation of contralateral Ins/SII during noxious cutaneous pressure stimulation of the foot was observed during infusion of anesthetic doses of propofol. 40 In the current study, in naïve macaques, no significant brain activation was observed up to 30 ml rectal distention and this could have been in part due to propofol anesthesia. More likely, however, is that the rectal distention volumes used in the current study were not noxious.…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“… 53 In a previous study in naïve macaques, significant activation of contralateral Ins/SII during noxious cutaneous pressure stimulation of the foot was observed during infusion of anesthetic doses of propofol. 40 In the current study, in naïve macaques, no significant brain activation was observed up to 30 ml rectal distention and this could have been in part due to propofol anesthesia. More likely, however, is that the rectal distention volumes used in the current study were not noxious.…”
Section: Discussioncontrasting
confidence: 43%
“…Macaques were sedated during each scan by infusion of a non‐analgesic dose of propofol (0.2 mg/kg/h; Maruishi Pharmaceutical). 38 , 39 , 40 Heads were fixed with an MR compatible acrylic head holder (Matsui Co.). During the scan, macaques were kept warm with blankets and heating pads.…”
Section: Methodsmentioning
confidence: 99%
“…35 Under propofol anesthesia, contralateral Ins/SII activation was observed with fMRI. 35 Thus, the von Frey filaments used in the current study, even though they evoked responses in awake uninjured macaques, can be considered non-noxious. Extracellular recordings of dorsal horn spinothalamic tract (STT) neurons have shown responding to a similar range of von Frey filaments when applied to the macaque foot, but these were not as robust to in response to either pressure or pinch.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to pain perception, a preclinical fMRI study in macaques found that noxious stimuli resulted in activation of the secondary somatosensory cortex and insula under propofol or pentobarbital anesthesia, whereas no activation was observed with isoflurane anesthesia. 40 In humans, ongoing nociceptive processing has been shown to occur in adolescent patients under balanced general anesthesia. 41 …”
Section: State Ii: Perioperative Approachesmentioning
confidence: 99%
“… 68 , 69 The two regions respond in an inverse manner to pain/nociception (mPFC deactivates and SI activates), thereby providing a suitable anticorrelative marker. The premise of our approach to the use of fNIRS during surgery is based on a number of themes: (1) animal, 70 including nonhuman primate 40 and human data 58 indicate that the pain pathways may be activated in the SI even under inhalational 71 and propofol 72 anesthesia; (2) surgical intervention, a controlled timed event, results in the potential initiation of chronic pain in a significant number of patients; (3) evaluation and response to pain during surgery are somewhat subjective and not based on specific/objective measures; and (4) an objective marker that allows for ongoing analgesia or immediate response to pain during the intra- and postoperative periods may provide an opportunity for diminished postoperative pain levels and risk of chronification (acute and chronic).
Figure 2.
…”
Section: State Ii: Perioperative Approachesmentioning
confidence: 99%